On Behalf Of The Visiting Firemen - Walter Donaldson::::::::: (Mercer & Morris, Inc.)
Piano and vocal score, 5 p. On cover: Official song, New York Worlds Fair 1940. Publishers advertisements on p.[2] and verso of last leaf.